The Effect of Gadget Addiction on the Ability to Read the Qur'an Among Students at Islamic Junior High Schools in Cirebon Regency - Abu Warasy Batula; Udin Supriadi; Nurti Budiyanti; Muhammadun Muhammadun (Lembaga Pengembangan Kinerja Dosen, 2025)
In the era of globalization, the widespread use of digital gadgets has significantly influenced students’ daily lives, including their learning processes. This study aims to evaluate the prevalence of gadget addiction among students at Madrasah Tsanawiyah (MTS) and to examine its potential impact on their ability to recite the Qur’an. A quantitative approach with a correlational research design was employed to identify the association between gadget addiction and Qur’an reading proficiency. The participants consisted of 122 students selected through convenience sampling from one MTS institution in Cirebon Regency. The instrument for measuring gadget addiction contained 11 items, while the Qur’an reading ability test consisted of 12 items, with a reliability coefficient of 0.593. Data analysis included descriptive statistics to describe the distribution of scores and inferential statistics, specifically the correlation test, to determine the relationship between the two variables. The results revealed that 77% of students experienced a high level of gadget addiction, while 15% demonstrated low levels, and 8% fell into the moderate category. In terms of Qur’an recitation ability, 63% of the students were classified in the low category, 35% in the moderate category, and only 2% in the high category. The correlation analysis produced a coefficient of -0.544**, indicating a moderately strong negative relationship between gadget addiction and Qur’an reading ability (range 0.400–0.599). The two-tailed significance value (p = 0.000 < 0.05) confirmed the statistical significance of this finding. Overall, the study highlights that greater gadget addiction is associated with lower Qur’an reading proficiency, whereas lower levels of gadget use are linked to improved recitation skills. These findings suggest the urgent need for educational interventions and parental guidance to balance gadget usage and ensure the strengthening of Qur’anic literacy among students.